Preparation method, application and application method of alkali-activated composite cement slump-retaining water reducer

By designing a slump-retaining water reducing agent in alkali-excited composite cement, and using the characteristics of phosphate groups and functional functional groups, the problem of poor fluid retention of alkali-excited composite cement is solved, and the long-term water reduction effect and construction performance of the material are improved.

CN119708377APending Publication Date: 2025-03-28HEBEI UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411935141.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In practical applications, alkali-excited composite cement faces the problem of poor fluid retention, which leads to rapid loss of material slump and affects construction operation.

Method used

A polycarboxylic acid water reducing agent containing phosphoric acid groups is prepared by configuring a base material, preparing material A and material B, and adding and insulating it at a specific temperature to prepare a polycarboxylic acid water reducing agent containing phosphoric acid groups. In the design, this method fully considers fly ash as the main component and cement as the secondary component, introduces functional functional groups, increases the adsorption effect of the water reducer in an alkaline environment, and reduces the flocculation between particles.

Benefits of technology

The water reducing agent prepared by this method can play a water reducing effect under alkaline conditions for a long time, delay the water loss of the gelled material, improve the material's collapse retention time, and ensure construction performance and final strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708377A_ABST
    Figure CN119708377A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of building material additives, in particular to a preparation method, application and application method of an alkali-activated composite cement slump-retaining water reducer, and the preparation method comprises the following steps: preparing a backing material, adding a phosphorylated macromonomer into a four-neck flask, adding deionized water, starting stirring to completely dissolve the phosphorylated macromonomer, adding H2O2, and continuously stirring for 2 minutes; the preparation method comprises the following steps: preparing a material A, adding acrylic acid and 2-methyl-2-acrylic acid-2-hydroxyethyl phosphate into deionized water, and dissolving; preparing a material B, and adding ascorbic acid and mercaptoacetic acid into deionized water for dissolving; respectively dropwise adding the material A and the material B into a four-neck flask, controlling the dropwise adding temperature to be 40-60 DEG C, and completing dropwise adding within 2.5-3 hours; after the material A and the material B are dropwise added and the heat preservation reaction is finished, cooling to room temperature to obtain the polycarboxylic acid alkali-activated composite cement slump retaining water reducing agent containing the phosphate group. Good dispersity and fluidity of the composite cement are maintained through the water reducing agent, the slump retention time is prolonged, and the construction performance of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building material additives, and in particular to a preparation method, application and application method of an alkali-activated composite cement slump-retaining water reducing agent. Background Art

[0002] As global environmental awareness continues to increase, the construction industry's demand for low-carbon, green building materials is growing. The traditional production process of silicate cement is accompanied by a large amount of carbon dioxide emissions, and its production process accounts for about 7-8% of global carbon emissions. At the same time, the amount of industrial solid waste (such as slag, fly ash, etc.) generated is also increasing year by year. How to efficiently utilize these wastes has become an environmental problem that needs to be solved urgently. Therefore, the development of a new type of cementitious material that can both reduce carbon emissions and utilize industrial solid waste on a large scale has become an important research direction in the current field of building materials.

[0003] Alkali-activated composite cement and alkali-activated cementitious materials both belong to the alkali-activated material system. Their common point is that they both contain alkaline activators and a large amount of industrial solid waste (such as slag, fly ash, kaolin, etc.), and significantly reduce carbon emissions during the production process. However, there are significant differences in their composition, performance and application areas. Compared with alkali-activated cementitious materials composed entirely of industrial solid waste, alkali-activated composite cement has the advantages of high early strength, better construction performance and less dependence on activators due to the small amount of silicate cement.

[0004] Although alkali-activated composite cement has many advantages, it still faces some technical challenges in practical application, and poor fluidity retention is one of the main problems. This is mainly because industrial waste materials (such as slag, fly ash, etc.) in the alkali-activated system often show high viscosity and fast coagulation characteristics during the hydration process, resulting in rapid loss of slump of the material, which seriously affects the construction operability. This problem restricts the promotion and application of alkali-activated composite cement in actual engineering.

[0005] In order to solve this key problem, the development of slump-preserving water-reducing agents specifically for alkali-activated composite cement has become the focus of technological breakthroughs.

[0006] Chinese Patent Publication No.: CN118459147A discloses an anti-cracking water reducing agent suitable for alkali-activated cement and its preparation process and application. The raw materials for the preparation of the anti-cracking water reducing agent include the following components: 500 parts of refined naphthalene, 200 parts of formaldehyde solution, 80 parts of dihydroxy-terminated dimethyl silicone oil, 100 parts of alkali solution, 15-20 parts of sodium dodecylbenzene sulfonate, 80-100 parts of sulfate solution, and 400 parts of water. It can be seen that the anti-cracking water reducing agent suitable for alkali-activated cement and its preparation process and application have the following problems:

[0007] The design of the molecular structure of the water reducer is not precise enough, and the application of the water reducer is not flexible enough. Summary of the invention

[0008] To this end, the present invention provides a preparation method, application and application method of an alkali-activated composite cement slump-retaining water reducer, so as to overcome the problems in the prior art that the design of the molecular structure of the water reducer is not accurate enough and the application of the water reducer is not flexible enough.

[0009] To achieve the above object, the present invention provides a method for preparing an alkali-activated composite cement slump-retaining water reducing agent, comprising:

[0010] Step S1, preparing the base material, adding the phosphorylated macromonomer into a four-necked flask, adding deionized water, stirring to completely dissolve it, adding H2O2 and continuing to stir for 2 minutes to obtain the base material;

[0011] Step S2, preparing material A, adding acrylic acid and 2-methyl-2-acrylic acid-2-hydroxyethyl phosphate into deionized water to dissolve, to obtain material A;

[0012] Step S3, preparing material B, adding ascorbic acid and thioglycolic acid into deionized water to dissolve, to obtain material B;

[0013] Step S4, respectively adding the above material A and material B dropwise into a four-necked flask, controlling the dropping temperature to be 40-60° C., and completing the dropping within 2.5-3 hours;

[0014] Step S5, after the dropwise addition of material A and material B is completed, the mixture is kept warm at 60° C. for 1.5 hours. After the reaction is completed, the mixture is cooled to room temperature to obtain a polycarboxylic acid alkali-activated composite cement slump-retaining and water-reducing agent containing a phosphate group.

[0015] Further, the phosphorylated macromonomer is prepared,

[0016] 300 g of methyl allyl alcohol (HPEG) or vinyl glycol ether (EPEG) is added to a reaction kettle, ethylene oxide (EO) and deionized water are added, the temperature of the reaction kettle is adjusted to 100-130° C., and about 0.05%-0.2% of a catalyst is added at a pressure of 2 Pa until the molecular weight reaches about 3000-4000; the temperature in the kettle is lowered to room temperature, 10.5-42 g of polyphosphoric acid is added to the reaction kettle and stirred for 1-3 hours to obtain a phosphorylated macromonomer HPEG-P or EPEG-P.

[0017] Further, the catalyst includes NaOH, KOH or other commonly used activators;

[0018] The molecular weight of the HPEG-P is 2400-3000, and the molecular weight of the EPEG-P is 3000-4000.

[0019] The general structural formula of HPEG-P and EPEG-P is as follows,

[0020] HPEG-P:

[0021] EPEG-P:

[0022] R is H n+1 P n O 3n .

[0023] Furthermore, the general structural formula of the polymer of the alkali-activated composite cement slump-retaining water-reducing agent is as follows, HPEG-P PCE:

[0024] EPEG-P PCE:

[0025] Furthermore, the alkali-activated composite cement slump-retaining water-reducing agent comprises, by weight, 100 parts of phosphorylated macromonomers, 5-12 parts of acrylic acid, 0.5 parts of small monomers containing phosphoric acid groups, 1.5 parts of H2O2, 0.3 parts of ascorbic acid, and 0.3-0.5 parts of chain transfer agents.

[0026] Further, the phosphorylated macromonomer is HPEG-P or EPEG-P;

[0027] The chain transfer agent is thioglycolic acid;

[0028] The phosphoric acid group small monomer is 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate.

[0029] Furthermore, the alkali-activated composite cement comprises the following components in parts by weight:

[0030] Fly ash (525-750 parts), slag (175-250 parts), standard cement (100-200 parts), water 300 parts, alkali activator 10 parts, polycarboxylate water reducer 1.5-3 parts;

[0031] The alkali activated composite cement further comprises the water reducing agent in an amount of 0.15% to 0.30% of the weight of the alkali activated composite cement and the alkali activator in an amount of 1% to 2% of the weight of the alkali activated composite cement;

[0032] The activator is selected from one or more of sodium silicate, potassium citrate, potassium carbonate and sodium citrate.

[0033] The present invention provides an application method for the above-mentioned alkali-activated composite cement slump-retaining water reducing agent, characterized in that the added content of the water reducing agent is confirmed by testing and analyzing a test piece of the alkali-activated composite cement, comprising:

[0034] Step S1, testing and analyzing the test piece of alkali-activated composite cement according to the initial detection cycle, judging whether the slump meets the construction requirements according to the fluidity of the test piece, and adding a water reducing agent during the preparation process of the test piece of alkali-activated composite cement according to the initial content;

[0035] Step S2, judging the degree of slump loss according to the fluidity difference between the actual fluidity detected in any initial detection cycle and the historical fluidity detected in the previous initial detection cycle, and adjusting the initial content of the water reducing agent added according to the degree of slump loss;

[0036] Step S3, detecting the final setting porosity of the alkali-activated composite cement specimen, determining the compressive strength of the alkali-activated composite cement according to the final setting porosity, and adjusting the temperature during the preparation process of the alkali-activated composite cement.

[0037] In the process of preparing the test specimens of alkali-activated composite cement, the fluidity of the test specimens of alkali-activated composite cement without adding collapse-preserving water-reducing agent is tested according to the initial test cycle, and the actual fluidity of the alkali-activated composite cement after the required time is tested.

[0038] If the actual fluidity is greater than or equal to the required fluidity, it is judged that the actual fluidity of the alkali-activated composite cement after the required time is large, and the slump can meet the construction requirements of the composite cement;

[0039] If the actual fluidity is less than the required fluidity, it is judged that the actual fluidity of the alkali-activated composite cement after the required time is small, and the slump does not meet the construction requirements of the composite cement;

[0040] Among them, the demand fluidity and the demand duration are preset values ​​set according to construction requirements.

[0041] Further, when the slump does not meet the construction requirements of the composite cement, a water reducing agent is added during the preparation of the test piece of the alkali-activated composite cement according to the initial content;

[0042] After adding the water reducing agent, the fluidity of the test piece of the alkali-activated composite cement to which the water reducing agent was added was tested according to the initial test cycle;

[0043] Calculate the mobility difference between the actual mobility detected in any initial detection cycle and the historical mobility detected in the previous initial detection cycle,

[0044] If the fluidity difference detected in any initial test cycle is less than or equal to the difference evaluation value, it is judged that the degree of fluidity reduction is small and the slump loss is small;

[0045] If the fluidity difference detected in any initial test cycle is greater than the difference evaluation value, it is judged that the fluidity is reduced to a greater extent and the slump loss is greater. The initial content of water reducing agent added is increased according to the ratio of the difference evaluation value to the fluidity difference;

[0046] Wherein, the initial content is 0.225% of the weight of the alkali-activated composite cement, and the difference evaluation value is a preset value set according to the fluidity test data of the test piece of the alkali-activated composite cement;

[0047] After adding water reducing agent, the final setting porosity of alkali-activated composite cement specimens was detected by scanning electron microscopy.

[0048] If the final setting porosity is less than or equal to the porosity under standard compressive strength, it is judged that the porosity of the alkali-activated composite cement is moderate and the compressive strength can meet the construction requirements;

[0049] If the final setting porosity is greater than the porosity at the standard compressive strength, it is judged that the porosity of the alkali-activated composite cement is large and the compressive strength does not meet the construction requirements. The temperature in the preparation process of the alkali-activated composite cement is increased according to the ratio of the final setting porosity to the porosity at the standard compressive strength.

[0050] Among them, the standard compressive strength is the compressive strength of the composite cement required for construction.

[0051] Compared with the prior art, the beneficial effect of the present invention lies in that, by fully considering fly ash as the main component and cement as the secondary component in the design, the present invention introduces functional functional groups, increases the adsorption effect of the water reducer in an alkaline environment, reduces the flocculation effect between particles, and ensures that it can exert its water reducing effect for a long time under alkaline conditions.

[0052] Furthermore, the present invention first prepares the phosphorylated macromonomer and H2O2 into the base material because: the reaction process is more efficient, and the base material (mixed system of macromonomer and small monomer) is mixed with the oxidant, which can make the monomers react more fully, improve the reaction efficiency and molecular structure stability, and make it easier to control the functionality of the carboxylic acid small monomer and the key parameters such as the molecular weight and degree of polymerization of the additive. At the same time, the functional additive synthesized by this method is more helpful to improve the dispersibility of the alkali-excited system slurry, thereby improving the early workability and homogeneity of the slurry, and has stronger adaptability.

[0053] Furthermore, the present invention prepares a new type of slump-retaining water-reducing agent suitable for alkali-activated composite cement through molecular design. Compared with the traditional polycarboxylic acid water-reducing agent, the alkali-activated composite cement slump-retaining water-reducing agent disclosed in the present invention has a longer side chain, which can delay the water loss of cementitious materials. The alkali-activated composite cement slump-retaining water-reducing agent disclosed in the present invention also has a phosphate group, which has stronger complexing ability and adsorption ability than the carboxylic acid group, and can still maintain good chemical stability in an alkaline environment, especially in an alkali-activated system. The dispersion effect is maintained for a long time, thereby extending the slump-retaining time of the material. In addition, the fly ash and slag provided by the present invention are used as the main raw materials, and cement is used as the secondary material, which increases the adsorption amount of the polycarboxylic acid water-reducing agent in the alkali-activated composite cement system, so that the water-reducing performance of the water-reducing agent is fully exerted, and the fly ash and slag will not have a negative impact on the compressive strength through the combination with cement and the activator.

[0054] Furthermore, the fluidity and slump of cement are important indicators for measuring the working performance of cement paste, which directly affect the construction performance and ultimate strength of concrete. The fluidity of the test pieces of alkali-activated composite cement is used to reflect the relationship between the slump of alkali-activated composite cement and the construction requirements of the composite cement, thereby determining the need to add water reducers to improve the fluidity and slump of the composite cement. When adding water reducers, the amount of water reducers needs to be strictly controlled. By calculating the difference in fluidity between the actual fluidity and the historical fluidity detected in the previous initial test cycle, the size of the slump loss can be judged to avoid excessive addition that may cause the cement paste to take too long to set or reduce its strength.

[0055] Furthermore, scanning electron microscopy was used to analyze the microstructure of alkali-activated slag-fly ash. The results showed that the slurry structure was relatively dense in the early stage of hydration, but a large amount of fly ash would accumulate, and as the amount of fly ash increased, the pores and microcracks would also increase. However, under high temperature conditions, the microstructure of the alkali-activated slag-fly ash material would change. Below 400°C, as the temperature increased, additional gel would be produced, making the overall structure more compact. The present invention uses the final setting porosity of the alkali-activated composite cement specimen to reflect the compressive strength of the composite cement, thereby adjusting the temperature during the preparation of the alkali-activated composite cement according to the ratio of the final setting porosity to the porosity at the standard compressive strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 The present invention is a flowchart of a method for preparing an alkali-activated composite cement collapse-preserving water-reducing agent according to an embodiment of the present invention;

[0057] Figure 2 Schematic diagram of fluidity detection of alkali-activated composite cement in an embodiment of the present invention;

[0058] Figure 3This is a flow chart for judging whether alkali-activated composite cement can meet the slump requirement in an embodiment of the present invention;

[0059] Figure 4 A flow chart for determining the slump loss of alkali-activated composite cement in an embodiment of the present invention;

[0060] In the figure: 1-conical mold. DETAILED DESCRIPTION

[0061] In order to make the objects and advantages of the present invention more clearly understood, the present invention is further described below in conjunction with embodiments; it should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0062] The preferred embodiments of the present invention are described below with reference to the accompanying drawings. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.

[0063] It should be noted that, in the description of the present invention, terms such as "up", "down", "left", "right", "inside" and "outside" indicating directions or positional relationships are based on the directions or positional relationships shown in the drawings. This is merely for the convenience of description and does not indicate or imply that the device or element must have a specific orientation, be constructed and operated in a specific orientation. Therefore, it cannot be understood as a limitation on the present invention.

[0064] In addition, it should be noted that in the description of the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For those skilled in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0065] See also Figure 1-Figure 4 As shown, Figure 1 The present invention is a flowchart of a method for preparing an alkali-activated composite cement collapse-preserving water-reducing agent according to an embodiment of the present invention; Figure 2 Schematic diagram of fluidity detection of alkali-activated composite cement in an embodiment of the present invention; Figure 3 This is a flow chart for judging whether alkali-activated composite cement can meet the slump requirement in an embodiment of the present invention; Figure 4 The present invention is a flow chart for determining the slump loss of alkali-activated composite cement in an embodiment of the present invention.

[0066] The present invention provides a method for preparing an alkali-activated composite cement collapse-preserving water-reducing agent, comprising:

[0067] Step S1, preparing the base material, adding the phosphorylated macromonomer into a four-necked flask, adding deionized water, stirring to completely dissolve it, adding H2O2 and continuing to stir for 2 minutes to obtain the base material;

[0068] Step S2, preparing material A, adding acrylic acid and 2-methyl-2-acrylic acid-2-hydroxyethyl phosphate into deionized water to dissolve, to obtain material A;

[0069] Step S3, preparing material B, adding ascorbic acid and thioglycolic acid into deionized water to dissolve, to obtain material B;

[0070] Step S4, respectively adding the above material A and material B dropwise into a four-necked flask, controlling the dropping temperature to be 40-60° C., and completing the dropping within 2.5-3 hours;

[0071] Step S5, after the dropwise addition of material A and material B is completed, the mixture is kept warm at 60° C. for 1.5 hours. After the reaction is completed, the mixture is cooled to room temperature to obtain a polycarboxylic acid alkali-activated composite cement slump-retaining and water-reducing agent containing a phosphate group.

[0072] The dissolving temperature during the preparation of the base material is 30-50°C; the dropping speed of the material A is 4.2-4.3 g / min; and the dropping speed of the material B is 0.42-0.43 g / min.

[0073] preparing the phosphorylated macromonomer,

[0074] 300 g of methyl allyl alcohol (HPEG) or vinyl glycol ether (EPEG) is added to a reaction kettle, ethylene oxide (EO) and deionized water are added, the temperature of the reaction kettle is adjusted to 100-130° C., and about 0.05%-0.2% of a catalyst is added at a pressure of 2 Pa until the molecular weight reaches about 3000-4000; the temperature in the kettle is lowered to room temperature, 10.5-42 g of polyphosphoric acid is added to the reaction kettle and stirred for 1-3 hours to obtain a phosphorylated macromonomer HPEG-P or EPEG-P.

[0075] Specifically, the present invention fully considers fly ash as the main component and cement as the secondary component in the design, introduces functional groups, increases the adsorption effect of the water reducer in an alkaline environment, and reduces the flocculation effect between particles, thereby ensuring that it can exert its water reducing effect for a long time under alkaline conditions.

[0076] In a preferred embodiment of the present invention, the catalyst includes NaOH, KOH or other commonly used activators;

[0077] The molecular weight of the HPEG-P is 2400-3000, and the molecular weight of the EPEG-P is 3000-4000.

[0078] The general structural formula of HPEG-P and EPEG-P is as follows,

[0079] HPEG-P:

[0080] EPEG-P:

[0081] R is H n+1 P n O 3n .

[0082] The general structural formula of the polymer of the alkali-activated composite cement slump-retaining water-reducing agent is as follows:

[0083] HPEG-P PCE:

[0084] EPEG-P PCE:

[0085] Specifically, the present invention first prepares the phosphorylated macromonomer and H2O2 into the base material because: the reaction process is more efficient, and the base material (mixed system of macromonomer and small monomer) is mixed with the oxidant, which can make the monomers react more fully, improve the reaction efficiency and molecular structure stability, and make it easier to control the functionality of the carboxylic acid small monomer and the key parameters such as the molecular weight and degree of polymerization of the additive. At the same time, the functional additive synthesized by this method is more helpful to improve the dispersibility of the slurry of the alkali-excited system, thereby improving the early workability and homogeneity of the slurry, and has stronger adaptability.

[0086] The alkali-activated composite cement slump-retaining water-reducing agent comprises, by weight, 100 parts of phosphorylated macromonomers, 5-12 parts of acrylic acid, 0.5 parts of phosphoric acid group-containing small monomers, 1.5 parts of H2O2, 0.3 parts of ascorbic acid, and 0.3-0.5 parts of chain transfer agents;

[0087] The phosphorylated macromonomer is HPEG-P or EPEG-P;

[0088] The chain transfer agent is thioglycolic acid;

[0089] The phosphoric acid group small monomer is 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate.

[0090] The alkali-activated composite cement comprises the following components in parts by weight: fly ash (525-750 parts), slag (175-250 parts), reference cement (100-200 parts), and 300 parts of water.

[0091] The alkali activated composite cement further comprises the water reducing agent in an amount of 0.15% to 0.30% of the weight of the alkali activated composite cement and the alkali activator in an amount of 1% to 2% of the weight of the alkali activated composite cement;

[0092] The activator is selected from one or more of sodium silicate, potassium citrate, potassium carbonate and sodium citrate.

[0093] The weight ratio of fly ash to slag in the alkali-activated composite cement is 3:1, the percentage of the base cement in the weight of the alkali-activated composite cement varies between 10% and 20%, the added amount of the activator is 1% of the weight of the alkali-activated composite cement, and the added amount of the polycarboxylate water-reducing agent is 0.15% to 0.3% of the weight of the alkali-activated composite cement.

[0094] Specifically, the present invention prepares a new type of slump-retaining water-reducing agent suitable for alkali-activated composite cement through molecular design. Compared with the traditional polycarboxylic acid water-reducing agent, the alkali-activated composite cement slump-retaining water-reducing agent disclosed in the present invention has a longer side chain, which can delay the water loss of cementitious materials. The alkali-activated composite cement slump-retaining water-reducing agent disclosed in the present invention also has a phosphate group, which has stronger complexing ability and adsorption ability than the carboxylic acid group, and can still maintain good chemical stability in an alkaline environment, especially in an alkali-activated system. The dispersion effect is maintained for a long time, thereby extending the slump-retaining time of the material. In addition, the fly ash and slag provided by the present invention are used as the main raw materials, and cement is used as the secondary material, which increases the adsorption amount of the polycarboxylic acid water-reducing agent in the alkali-activated composite cement system, so that the water-reducing performance of the water-reducing agent is fully exerted, and the fly ash and slag will not have a negative impact on the compressive strength through the combination with cement and the activator.

[0095] The present invention provides an application method for the above-mentioned alkali-activated composite cement slump-retaining water reducing agent, characterized in that the added content of the water reducing agent is confirmed by testing and analyzing a test piece of the alkali-activated composite cement, comprising:

[0096] Step S1, testing and analyzing the test piece of alkali-activated composite cement according to the initial detection cycle, judging whether the slump meets the construction requirements according to the fluidity of the test piece, and adding a water reducing agent during the preparation process of the test piece of alkali-activated composite cement according to the initial content;

[0097] Step S2, judging the degree of slump loss according to the fluidity difference between the actual fluidity detected in any initial detection cycle and the historical fluidity detected in the previous initial detection cycle, and adjusting the initial content of the water reducing agent added according to the degree of slump loss;

[0098] Step S3, detecting the final setting porosity of the alkali-activated composite cement specimen, determining the compressive strength of the alkali-activated composite cement according to the final setting porosity, and adjusting the temperature during the preparation process of the alkali-activated composite cement.

[0099] In this embodiment, the alkali-activated composite cement is a slag / fly ash-based composite system.

[0100] In the process of preparing the test specimens of alkali-activated composite cement, the fluidity of the test specimens of alkali-activated composite cement without adding collapse-preserving water-reducing agent is tested according to the initial test cycle, and the actual fluidity of the alkali-activated composite cement after the required time is tested.

[0101] If the actual fluidity is greater than or equal to the required fluidity, it is judged that the actual fluidity of the alkali-activated composite cement after the required time is large, and the slump can meet the construction requirements of the composite cement;

[0102] If the actual fluidity is less than the required fluidity, it is judged that the actual fluidity of the alkali-activated composite cement after the required time is small, and the slump does not meet the construction requirements of the composite cement.

[0103] Among them, the demand fluidity and the demand duration are preset values ​​set according to construction requirements.

[0104] The fluidity of the alkali-activated composite cement specimen is tested by using a conical mold 1 with a lower depth of 38 mm, an upper depth of 9 mm, and a height of 57 mm. The fresh slurry is immediately poured into the mold, and the mold is slowly lifted vertically upward. The slurry flows freely to obtain the fluidity of the alkali-activated composite cement. The test is performed every half an hour, and the fluidity results within two hours are recorded.

[0105] When the slump does not meet the construction requirements of composite cement, water reducing agent is added during the preparation of the test piece of alkali activated composite cement according to the initial content;

[0106] After adding the water reducing agent, the fluidity of the test piece of the alkali-activated composite cement to which the water reducing agent was added was tested according to the initial test cycle;

[0107] Calculate the mobility difference between the actual mobility detected in any initial detection cycle and the historical mobility detected in the previous initial detection cycle,

[0108] If the fluidity difference detected in any initial test cycle is less than or equal to the difference evaluation value, it is judged that the degree of fluidity reduction is small and the slump loss is small;

[0109] If the fluidity difference detected in any initial test cycle is greater than the difference evaluation value, it is judged that the fluidity is reduced to a large extent and the slump loss is large. The initial content of water reducer is increased according to the ratio of the difference evaluation value to the fluidity difference.

[0110] The initial content is 0.225% of the weight of the alkali-activated composite cement, and the difference evaluation value is a preset value set according to the fluidity detection data of the test piece of the alkali-activated composite cement.

[0111] Specifically, the fluidity and slump of cement are important indicators for measuring the working performance of cement paste, which directly affect the construction performance and ultimate strength of concrete. The fluidity of alkali-activated composite cement specimens is used to reflect the relationship between the slump of alkali-activated composite cement and the construction requirements of composite cement, thereby determining the need to add water reducers to improve the fluidity and slump of composite cement. When adding water reducers, the amount of water reducers needs to be strictly controlled, and the size of the slump loss can be determined by calculating the difference in fluidity between the actual fluidity and the historical fluidity detected in the previous initial test cycle, so as to avoid excessive addition that may cause the cement paste to take too long to set or reduce its strength.

[0112] After adding water reducing agent, the final setting porosity of alkali-activated composite cement specimens was detected by scanning electron microscopy.

[0113] If the final setting porosity is less than or equal to the porosity under standard compressive strength, it is judged that the porosity of the alkali-activated composite cement is moderate and the compressive strength can meet the construction requirements;

[0114] If the final setting porosity is greater than the porosity under the standard compressive strength, it is judged that the porosity of the alkali-activated composite cement is large and the compressive strength does not meet the construction requirements. The temperature during the preparation of the alkali-activated composite cement is increased according to the ratio of the final setting porosity to the porosity under the standard compressive strength.

[0115] Among them, the standard compressive strength is the compressive strength of the composite cement required for construction.

[0116] Specifically, the microstructure of alkali-activated slag-fly ash was analyzed using a scanning electron microscope. The results showed that the slurry structure was relatively dense in the early stage of hydration, but a large amount of fly ash would accumulate, and as the amount of fly ash increased, the pores and microcracks would also increase. However, under high temperature conditions, the microstructure of the alkali-activated slag-fly ash material would change. Below 400°C, as the temperature increased, additional gel would be produced, making the overall structure more dense. The present invention uses the final setting porosity of the alkali-activated composite cement specimen to reflect the compressive strength of the composite cement, thereby adjusting the temperature during the preparation of the alkali-activated composite cement according to the ratio of the final setting porosity to the porosity at the standard compressive strength.

[0117] Preparation Example 1:

[0118] 100 g of HPEG-P-1 (molecular weight of about 3000) was added to a four-necked flask, deionized water was added, and stirring was started to completely dissolve it; 1.54 g of 30% hydrogen peroxide solution was added, and a deionized water droplet A containing 12.0 g of acrylic acid (acid-ether ratio of 5.0) and 0.515 g of 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate was prepared, and a deionized water droplet solution B containing 0.3 g of ascorbic acid and 0.5 g of thioglycolic acid was prepared; the above droplets A and B were respectively added dropwise to the four-necked flask, and the dropping temperature was controlled to be 40-60° C., and the dripping was completed in 2.5-3 hours. After the dropwise addition was completed, it was kept warm at 60° C. for 1.5 hours. After the reaction was completed, it was cooled to room temperature to obtain a polycarboxylic acid water reducer product HPEG-PCE1 containing a phosphate group.

[0119] The sample was tested by GPC and the molecular weight was 49698, the molecular weight distribution was 1.31, and the solid content was 50.56%.

[0120] Preparation Example 2:

[0121] 100 g of HPEG-P-2 (molecular weight of about 2400) was added to a four-necked flask, deionized water was added, and stirring was started to completely dissolve it; 1.54 g of 30% hydrogen peroxide solution was added, and a deionized water droplet A containing 9.9 g of acrylic acid (acid-ether ratio of 3.3) and 0.515 g of 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate was prepared, and a deionized water droplet solution B containing 0.3 g of ascorbic acid and 0.4 g of thioglycolic acid was prepared; the above droplets A and B were respectively added dropwise to the four-necked flask, and the dropping temperature was controlled to be 40-60° C., and the dripping was completed in 2.5-3 hours. After the dropwise addition was completed, it was kept warm at 60° C. for 1.5 hours. After the reaction was completed, it was cooled to room temperature to obtain a polycarboxylic acid water-reducing agent product HPEG-PCE2 containing a phosphate group.

[0122] The sample was tested by GPC and the molecular weight was 46524, the molecular weight distribution was 1.45, and the solid content was 53.44%.

[0123] Preparation Example 3:

[0124] 100 g of HPEG-P-3 (molecular weight of about 3000) was added to a four-necked flask, deionized water was added, and stirring was started to completely dissolve it; 1.54 g of 30% hydrogen peroxide solution was added, and a deionized water droplet A containing 7.9 g of acrylic acid (acid-ether ratio of 3.3) and 0.515 g of 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate was prepared, and a deionized water droplet solution B containing 0.3 g of ascorbic acid and 0.5 g of thioglycolic acid was prepared; the above droplets A and B were respectively added dropwise to the four-necked flask, and the dropping temperature was controlled to be 40-60° C., and the dripping was completed in 2.5-3 hours. After the dripping was completed, it was kept warm at 60° C. for 1.5 hours. After the reaction was completed, it was cooled to room temperature to obtain a polycarboxylic acid water-reducing agent product HPEG-PCE3 containing a phosphate group.

[0125] The sample was tested by GPC and the molecular weight was 47271, the molecular weight distribution was 1.33, and the solid content was 49.83%.

[0126] Preparation Example 4:

[0127] 100 g of HPEG-P-4 (molecular weight of about 3000) was added to a four-necked flask, deionized water was added, and stirring was started to completely dissolve it; 1.54 g of 30% hydrogen peroxide solution was added, and a deionized water droplet A containing 11.0 g of acrylic acid (acid-ether ratio of 4.6) and 0.515 g of 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate was prepared, and a deionized water droplet solution B containing 0.3 g of ascorbic acid and 0.46 g of thioglycolic acid was prepared; the above droplets A and B were respectively added dropwise to the four-necked flask, and the dropping temperature was controlled to be 40-60° C., and the dripping was completed in 2.5-3 hours. After the dropwise addition was completed, it was kept warm at 60° C. for 1.5 hours. After the reaction was completed, it was cooled to room temperature to obtain a polycarboxylic acid water reducer product HPEG-PCE4 containing a phosphate group.

[0128] The sample was tested by GPC and the molecular weight was 64662, the molecular weight distribution was 1.14, and the solid content was 50.25%.

[0129] Preparation Example 5:

[0130] 100 g of EPEG-P-1 (molecular weight of about 4000) was added to a four-necked flask, deionized water was added, and stirring was started to completely dissolve it; 1.54 g of 30% hydrogen peroxide solution was added, and a deionized water droplet A containing 4.1 g of acrylic acid (acid-ether ratio of 2.3) and 0.515 g of 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate was prepared, and a deionized water droplet solution B containing 0.3 g of ascorbic acid and 0.33 g of thioglycolic acid was prepared; the above droplets A and B were respectively added dropwise to the four-necked flask, and the dropping temperature was controlled to be 5-15° C., and the dripping was completed in 1-3 hours. After the dripping was completed, it was kept warm at 35° C. for 1.5 hours. After the reaction was completed, it was cooled to room temperature to obtain the polycarboxylic acid water reducer product EPEG-PCE1 containing a phosphate group.

[0131] The sample was tested by GPC and the molecular weight was 58398, the molecular weight distribution was 1.35, and the solid content was 40.12%.

[0132] Preparation Example 6:

[0133] 100 g of EPEG-P-2 (molecular weight of about 4000) was added to a four-necked flask, deionized water was added, and stirring was started to completely dissolve it; 1.54 g of 30% hydrogen peroxide solution was added, and a deionized water droplet A containing 5.4 g of acrylic acid (acid-ether ratio of 3.0) and 0.515 g of 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate was prepared, and a deionized water droplet solution B containing 0.3 g of ascorbic acid and 0.33 g of thioglycolic acid was prepared; the above droplets A and B were respectively added dropwise to the four-necked flask, and the dropping temperature was controlled to be 5-15° C., and the dripping was completed in 1-3 hours. After the dropwise addition was completed, it was kept warm at 35° C. for 1.5 hours. After the reaction was completed, it was cooled to room temperature to obtain the polycarboxylic acid water-reducing agent product EPEG-PCE2 containing a phosphate group.

[0134] The sample was tested by GPC and the molecular weight was 63320, the molecular weight distribution was 1.41, and the solid content was 44.77%.

[0135] Preparation Example 7:

[0136] 100 g of EPEG-P-3 (molecular weight of about 3000) was added to a four-necked flask, deionized water was added, and stirring was started to completely dissolve it; 1.54 g of 30% hydrogen peroxide solution was added, and a deionized water droplet A containing 9.8 g of acrylic acid (acid-ether ratio of 4.1) and 0.515 g of 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate was prepared, and a deionized water droplet solution B containing 0.3 g of ascorbic acid and 0.46 g of thioglycolic acid was prepared; the above droplets A and B were respectively added dropwise to the four-necked flask, and the dropping temperature was controlled to be 5-15° C., and the dripping was completed in 1-3 hours. After the dripping was completed, it was kept warm at 35° C. for 1.5 hours. After the reaction was completed, it was cooled to room temperature to obtain the polycarboxylic acid water-reducing agent product EPEG-PCE3 containing a phosphate group.

[0137] The sample was tested by GPC and the molecular weight was 50048, the molecular weight distribution was 1.35, and the solid content was 50.00%.

[0138] The monomers and amounts of the water reducing agents used in the above-mentioned Preparation Examples 1 to 7 are shown in Table 1 below:

[0139] Preparation Example M Mn Acid-ether ratio HPEG-PCE1 49698 37966 5.0 HPEG-PCE2 43524 30011 3.3 HPEG-PCE3 47271 35536 3.3 HPEG-PCE4 64662 45872 4.6 EPEG-PCE1 58398 43156 2.3 EPEG-PCE2 63320 44934 3.0 EPEG-PCE3 50048 36976 4.1

[0140] Table 1

[0141] Example 1: The polycarboxylate water-reducing agent obtained in Preparation Example 1 is applied to an alkali-activated composite cement system, wherein the alkali-activated composite cement comprises the following raw materials by weight: fly ash (525-750 parts), slag (175-250 parts), reference cement (100-200 parts), alkali activator 10-20 parts, and water 300 parts. The preparation of the alkali-activated composite cement comprises the following steps:

[0142] (1) Mix the activator with 90% water and let it stand for 12-24 hours to obtain an activator solution;

[0143] (2) mixing the polycarboxylate water reducer obtained in Preparation Example 1 with 10% water to obtain a water reducer solution;

[0144] (3) Fly ash, slag and cement are fully mixed and stirred for 60 seconds to obtain powder mixture I;

[0145] (4) Pour the activator solution obtained in step (1) into the mixture I, stir for 10 seconds, then pour the water reducer solution in step (2) into the mixture I, stir for 6 minutes, and obtain an alkali-activated composite cement paste for testing.

[0146] Embodiment 2-7:

[0147] According to Example 1, the polycarboxylate water-reducing agent used in step (2) of Example 1 was replaced with the polycarboxylate water-reducing agents corresponding to Preparation Examples 2-7 in sequence, and the remaining steps were consistent with Example 1.

[0148] Comparative Example 1:

[0149] According to Example 1, the polycarboxylate water-reducing agent used in step (2) of Example 1 was replaced by water in an equal amount, and the remaining steps remained unchanged.

[0150] Comparative Example 2:

[0151] According to Example 1, the polycarboxylate water-reducing agent used in step (2) of Example 1 was replaced with commercially available polycarboxylate water-reducing agents in sequence, and the remaining steps were kept consistent with Example 1.

[0152] Performance test method: Use a conical mold 1 with a lower depth of 38 mm, an upper depth of 9 mm, and a height of 57 mm, immediately pour the obtained fresh slurry into the mold, slowly lift the mold vertically upward, and the slurry flows freely to obtain the fluidity of the alkali-activated composite cement. Test once every half an hour, and record the fluidity results within two hours. The results are shown in Table 2.

[0153] 0min 30min 60min 90min 120min HPEG-PPCE1 155 120 47.5 39 - HPEG-PPCE2 160 140 130 90 47.5 HPEG-PPCE3 150 142.5 122.5 65 - HPEH-PPCE4 160 135 67.5 40 - EPEG-PPCE1 90 110 125 127.5 120 EPEG-PPCE2 130 140 130 55 45 EPEG-PPCE3 160 137.5 87.5 47.5 45 Comparative Example 1 38 - - - - Comparative Example 2 130 120 75 45 -

[0154] Table 2

[0155] It can be seen from Tables 1 and 2 that the slump retention performance of the water reducer synthesized by EPEG is better than that of the water reducer synthesized by HPEG.

[0156] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.

[0157] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an alkali-activated composite cement collapse-preserving water reducer, characterized in that: include: Prepare the base material, add the phosphorylated macromonomer into a four-necked flask, add deionized water, start stirring to completely dissolve it, add H2O2 and continue stirring for 2 minutes to obtain the base material; Prepare material A by adding acrylic acid and 2-methyl-2-acrylic acid-2-hydroxyethyl phosphate into deionized water to dissolve to obtain material A; Prepare material B by adding ascorbic acid and thioglycolic acid into deionized water to dissolve them to obtain material B; Add the above material A and material B dropwise into a four-necked flask, control the dropping temperature to 40-60°C, and finish dropping within 2.5-3 hours; After the addition of material A and material B is completed, the mixture is kept warm at 60° C. for 1.5 hours. After the reaction is completed, the mixture is cooled to room temperature to obtain a polycarboxylic acid alkali-activated composite cement slump-retaining and water-reducing agent containing a phosphate group.

2. The method for preparing the alkali-activated composite cement slump-retaining water reducing agent according to claim 1, characterized in that: preparing the phosphorylated macromonomer, Add 300g of methyl allyl alcohol or vinyl glycol ether into a reactor, add ethylene oxide and deionized water, adjust the reactor temperature to 100°C, and add about 0.05%-0.2% of a catalyst at a pressure of 2Pa until the molecular weight reaches about 3000-4000; At room temperature, 10.5-42 g of polyphosphoric acid is added to a reaction kettle with stirring to obtain phosphorylated macromonomer HPEG-P or EPEG-P.

3. The preparation method of the alkali-activated composite cement slump-retaining water reducing agent according to claim 2, characterized in that: The catalyst includes NaOH, KOH or other commonly used activators; The molecular weight of HPEG-P is 2400-3000, and the molecular weight of EPEG-P is 3000-4000; The general structural formula of HPEG-P and EPEG-P is as follows, HPEG-P: EPEG-P: R is H n+1 P n O 3n .

4. The method for preparing the alkali-activated composite cement slump-retaining water reducing agent according to claim 1, characterized in that: The general structural formula of the polymer of the alkali-activated composite cement slump-retaining water-reducing agent is as follows: HPEG-P PCE: EPEG-P PCE:

5. The method for preparing the alkali-activated composite cement slump-retaining water reducing agent according to claim 1, characterized in that: The alkali-activated composite cement slump-retaining water-reducing agent comprises, by weight, 100 parts of phosphorylated macromonomers, 5-12 parts of acrylic acid, 0.5 parts of small monomers containing phosphoric acid groups, 1.5 parts of H2O2, 0.3 parts of ascorbic acid, and 0.3-0.5 parts of chain transfer agents.

6. The method for preparing the alkali-activated composite cement slump-retaining water reducing agent according to claim 5, characterized in that: The phosphorylated macromonomer is HPEG-P or EPEG-P; The chain transfer agent is thioglycolic acid; The phosphoric acid group small monomer is 2-methyl-2-acrylic acid-2-hydroxyethyl ester phosphate.

7. An application of an alkali-activated composite cement slump-retaining water reducer, wherein the slump-retaining water reducer is applied to the preparation process of alkali-activated composite cement, wherein: The slump-retaining water reducer is a water reducer prepared by the method for preparing the alkali-activated composite cement slump-retaining water reducer according to any one of claims 1 to 6.

8. An application method for the alkali-activated composite cement slump-retaining water reducing agent according to claims 1 to 6, characterized in that: include: The test pieces of alkali activated composite cement are tested and analyzed according to the initial test cycle, and the slump is judged according to the fluidity of the test pieces whether it meets the construction requirements, and a water reducing agent is added during the preparation of the test pieces of alkali activated composite cement according to the initial content; The degree of slump loss is determined based on the difference in fluidity between the actual fluidity detected in any initial test cycle and the historical fluidity detected in the previous initial test cycle, and the initial content of water reducing agent added is adjusted based on the degree of slump loss; The final setting porosity of the alkali-activated composite cement specimen is detected, the compressive strength of the alkali-activated composite cement is determined according to the final setting porosity, and the temperature during the preparation of the alkali-activated composite cement is adjusted.

9. The application method of the alkali-activated composite cement slump-retaining water reducing agent according to claim 8, characterized in that: In the process of preparing the test specimens of alkali-activated composite cement, the fluidity of the test specimens of alkali-activated composite cement without adding collapse-preserving water-reducing agent is tested according to the initial test cycle, and the actual fluidity of the alkali-activated composite cement after the required time is tested. If the actual fluidity is greater than or equal to the required fluidity, it is judged that the actual fluidity of the alkali-activated composite cement after the required time is large, and the slump can meet the construction requirements of the composite cement; If the actual fluidity is less than the required fluidity, it is judged that the actual fluidity of the alkali-activated composite cement after the required time is small, and the slump does not meet the construction requirements of the composite cement; Among them, the demand fluidity and the demand duration are preset values ​​set according to construction requirements.

10. The application method of the alkali-activated composite cement slump-retaining water reducing agent according to claim 9, characterized in that: When the slump does not meet the construction requirements of composite cement, water reducing agent is added during the preparation of the test piece of alkali activated composite cement according to the initial content; After adding the water reducing agent, the fluidity of the test piece of the alkali-activated composite cement to which the water reducing agent was added was tested according to the initial test cycle; Calculate the mobility difference between the actual mobility detected in any initial detection cycle and the historical mobility detected in the previous initial detection cycle, If the fluidity difference detected in any initial test cycle is less than or equal to the difference evaluation value, it is judged that the degree of fluidity reduction is small and the slump loss is small; If the fluidity difference detected in any initial test cycle is greater than the difference evaluation value, it is judged that the fluidity is reduced to a greater extent and the slump loss is greater. The initial content of water reducing agent added is increased according to the ratio of the difference evaluation value to the fluidity difference; Wherein, the initial content is 0.225% of the weight of the alkali-activated composite cement, and the difference evaluation value is a preset value set according to the fluidity test data of the test piece of the alkali-activated composite cement; After adding water reducing agent, the final setting porosity of alkali-activated composite cement specimens was detected by scanning electron microscopy. If the final setting porosity is less than or equal to the porosity under standard compressive strength, it is judged that the porosity of the alkali-activated composite cement is moderate and the compressive strength can meet the construction requirements; If the final setting porosity is greater than the porosity at the standard compressive strength, it is judged that the porosity of the alkali-activated composite cement is large and the compressive strength does not meet the construction requirements. The temperature in the preparation process of the alkali-activated composite cement is increased according to the ratio of the final setting porosity to the porosity at the standard compressive strength. The standard compressive strength is the compressive strength of the composite cement required for construction.

Citation Information

Patent Citations

  • Anti-cracking water reducing agent suitable for alkali-activated cement as well as preparation process and application of anti-cracking water reducing agent

    CN118459147A

  • Slump retaining type water reducing agent containing polyether phosphate monomer and preparation method thereof

    CN111234201A

  • Mud-resistant slump-retaining polycarboxylic acid water reducing agent as well as preparation method and application thereof

    CN114133495A

  • Ultrahigh-temperature-resistant and high-MB-value-resistant adsorption type polycarboxylate superplasticizer and preparation method thereof

    CN116102283A

  • Phosphoric acid group-containing polycarboxylate superplasticizer as well as preparation method and application thereof

    CN117903378A